Poverty in Maine - Acheson, Ann (Maine Policy Review, 2007)
Despite decades of concerted federal, state, local and private effort, poverty persists in Maine and many parts of the nation. The face of poverty, however, differs across regions and states. Maine, for example, has a higher rate of working poor than in the nation as a whole. In this article, Ann Acheson updates the profile of poverty in Maine, examining recent trends and the nature of regional disparities. Some measures of economic distress have worsened over the last five years; others remain stagnant. Acheson concludes with a brief overview of current policies and programs that address poverty and calls for a multifaceted approach to continuing poverty reduction efforts at all levels of government and in the private sector.
Keywords: Maine poverty; poverty policy; poverty benefits